2011
DOI: 10.1016/j.bios.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of influenza A virus infection utilizing an immunomagnetic bead-based microfluidic system

Abstract: This study reports a new immunomagnetic bead-based microfluidic system for the rapid detection of influenza A virus infection by performing a simple two-step diagnostic process that includes a magnetic bead-based fluorescent immunoassay (FIA) and an end-point optical analysis. With the incorporation of monoclonal antibody (mAb)-conjugated immunomagnetic beads, target influenza A viral particles such as A/H1N1 and A/H3N2 can be specifically recognized and are bound onto the surface of the immunomagnetic beads f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 28 publications
0
51
0
Order By: Relevance
“…The exact tracing of virions to the cells that have produced them also requires the analysis of individual viral particles. Currently, the envelope composition of viruses is studied by analyzing viral preparations in bulk, although attempts to visualize viruses using flow cytometers have been made (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The exact tracing of virions to the cells that have produced them also requires the analysis of individual viral particles. Currently, the envelope composition of viruses is studied by analyzing viral preparations in bulk, although attempts to visualize viruses using flow cytometers have been made (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Many optofluidic systems use the magnetic properties of particles for eventual bioapplications. An example of such manipulation is presented in the work of Lien et al 197 They used antibody conjugated magnetic beads (Ø4.5 lm) to detect and isolate influenza A viruses. Target influenza A virus, which was immobilized onto the surface of the magnetic beads.…”
Section: Optofluidics For the Transport And Analyses Of Biological Comentioning
confidence: 99%
“…Magnetic-bead-based methods for the separation and enrichment of targets include two types: specific and non-specific separations. Currently, the most widely used application is specific separation; this technology has been used in biomedical applications [8][9][10], food safety [11,12], environmental monitoring [13,14], and plant virus detection [15]. Previous studies have shown the development of magnetic-bead-based methods for the detection of CGMMV; this virus was successfully detected in cucumber seeds through specific virus adsorption with immunomagnetic beads (IMB) (coated with CGMMV antibody) followed by RT-PCR [16] and in cucumber leaves using an RT-PCR method combined with non-specific magnetic separation (MNP) (no CGMMV antibody coating) [17].…”
mentioning
confidence: 99%